Customised Microporous Carbon 3D Structures with Good Mechanical Properties and High Nitrogen Content Obtained from Whey Powders - Raúl Llamas-Unzueta; Luis A. Ramírez-Montoya; J. Angel Menéndez; Miguel A. Montes-Morán (C, 2023)
Novel customised carbon monoliths with a high specific surface area were synthesised by carbonisation plus activation of dehydrated whey powders, a biomass byproduct of the dairy industry. The whey powders were casted directly by pouring them into a desired mould. After a pseudo-sintering process promoted by the self-reaction of the whey components (mostly lactose and whey proteins) at moderate temperatures (ca. 250 °C), 3D porous carbons were obtained. The process did not require any binder or external overpressure to prepare the 3D porous carbons. Upon thermal activation with CO2 or chemical activation with H3PO4 and KOH, the shape of the monolithic structure was preserved after the development of a microporous network (SBET up to 2400 m2/g). Both thermal and chemical activation had little effect on the macroporosity of the monoliths. Activation of these 3D carbons had to be performed with care to avoid heterogeneous skin/core activation and/or overactivation. Highly porous monoliths (SBET of 980 m2/g; open porosity of 70%) with outstanding compressive strength (10 MPa) could be obtained by thermal activation (CO2) of whey monoliths at 850 °C for 1.5 h. Additionally, the use of whey as a precursor provided the carbon monolith with a relatively high nitrogen content (ca. 3 wt.%).